Micro-nano technology XVI selected, peer reviewed papers from the 16th Annual Conference and 5th International Conference of the Chinese Society of Micro-Nano Technology (CSMNT 2014), August 31-September 3, 2014, Chengdu, China - Tang, Fei (Key engineering materials, 2015)
Collection of selected, peer reviewed papers from the 16th Annual Conference and 5th International Conference of the Chinese Society of Micro-Nano Technology (CSMNT 2014), August 31-September 3, 2014, Chengdu, China.